6, 6-Fused heterocyclic ureas as highly potent TRPV1 antagonists. Issue 4 (15th February 2015) - Sun, Wei; Kim, Hyo-Shin; Lee, Sunho; Jung, Aeran; Kim, Sung-Eun; Ann, Jihyae; Yoon, Suyoung; Choi, Sun; Lee, Jin Hee; Blumberg, Peter M.; Frank-Foltyn, Robert; Bahrenberg, Gregor; et al.
Graphical abstract Compound 15Ki(ant) = 0.2 nM.